Pengaruh Struktur Modal, Kebijakan Dividen Dan Inflasi Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Sub Sektor Tekstil Dan Garmen Di Bei Pada Tahun 2016-2018) - Ayu Trisnawati; Ronny Malavia Mardani; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThe purpose of this research was to specify impact of Capital Fabric, Dividend Policy, and Inflation on Company Values (study on textile and garment sub-sector companies listed on the IDX in the year of 2016-2018) The population using this research were manufacturing companies in textile and garment sub-sector listed on the Indonesia Stock Exchange in 2016-2018. The sample used in research is a technique purposive sampling. Corporation that enter the research criteria consist of 17 companies over a 3 year period. The data collection method employed in research is documentations the monetary statements of manufacturing companies in the textile and garment sub-sector listed on the IDX. While the analysis of employed is multiple linear regression by testing the hypothesis using the T test. The output of the research explain the variable Capital Structure has a positive and significant influence on Company Value. Dividend policy has a positive and significant impact on Company denomination. While inflation has no significant effect on firm denomination. Keywords: Capital Structure, Dividend Policy, Inflation and Firm Value